Final distribution density of material fragment sizes at slow fragmentation process - Brodskii, R.Ye.; Virchenko, Yu.P. (Вопросы атомной науки и техники, 2012)
The process of slow material fragmentation is studied when the diffusion approximation is applicable. Final distribution density of fragment sizes is calculated in the case of scale-homogeneity of subdivision mechanism.